INTERACTION BETWEEN DUAL TEACHING MEDIA AND MOTIVATION ON THE STUDENTS’ LISTENING ACHIEVEMENT - Wiwin Pratiwi Harsa; Amrin . Saragih; Rahmad . Husein (Universitas Negeri Medan, 2021)
ABSTRACTThe objectives of this study are to describe the interaction between the results of teaching by audio visual and audio teaching media, and motivation towards the students’ listening. The research design was experimental research by using factorial design 2x2. There were 64 students from grade eighth in 2020/2021 academic year of SMP Al Washliyah 8 Medan as sample of this research. The students were divided into two groups. The first group was treated by using audio visual media and the second group was treated by using audio media. The motivation test was conducted for classifying the students upon the high and low motivation by using questionnaire. Students’ achievement in listening was measured by using multiple choice tests. The data were analyzed by applying Two-ways ANOVA, the results revealed that students’ listening achievement taught by using audio visual media significantly higher than that taught by using audio media and students’ listening achievement with high motivation was higher than students with low motivation. There was significant interaction between dual teaching media and motivation on the students’ listening achievement with Fobserved is lower than Ftable at the level significance α = 0.05 (Fobs = 1.76 < Ftab = 2.81) however, the value of significant level is α = 0.19 higher than 0.05. Thus, both teaching media and motivation significantly affect the students’ listening achievement.Keywords: Teaching Listening, Audio Visual Media, Audio Media, Motivation, Listening Achievement.